Residents and their trees: a quali-quantitative study of preferences, attitudes and social factors affecting trees planted in private yards in China - Zhang, Ang; Vesk, Peter A.; Grose, Margaret J. (Trees (Berlin, West), 2024)
Trees in private yards are subject to a complex assortment of interacting ecological, social, cultural and economic factors, including individual preferences, social networks, multiple stakeholders and social constraints. This study explored residents’ attitudes towards yard trees in China and determined the social factors shaping yard trees and yard tree planting. Nearly 300 questionnaires were collected in-person and online in urban and rural villages and communities in Zhoukou city, Henan. Most trees planted in yards were intentionally planted. Yard size was the main constraint on the number of trees in a yard with respondents repeatedly citing the lack of space as a deterrent to planting trees or planting more trees. The most popular attributes for trees planted in yards were symbolism and edibility. Residents’ attitudes were based upon tree functions. The willingness and attitudes of residents towards yard trees suggested that an increase in yard trees would be supported by residents, who appeared to be yearning for a green living environment. However, a lack of preference found for native species suggests a challenging future for native trees in yards in regard to their role in biodiversity and habitat formation. Men played the dominant role in activities associated with yard trees. Residents were keen to aid wider ambitions for greening through their own tree planting in yards, but need guidance via policies and incentives. Such moves at high levels of government will assist the achievement of sustainable development goals in the future China, such as increased city canopy and carbon targets.